Svarāja yātrānā mārā sāthī Śrī Ḍhebarabhāī - Joshi, Chhaganlal, 1895- (Sābaramatī Āśrama Surakshā ane Smāraka Ṭrasṭa ; prāptisthāna Harijana Sevaka Saṅgha, 1980)
Biography of Uchharangrai Navalshanker Dhebar, 1905-1977, Indian freedom fighter and political activist.